Correlation between phosphate level and Peritoneal Equilibration Test (PET) characteristics among Continuous Ambulatory Peritoneal Dialysis (CAPD) patients in HTAA, Kuantan - Rajiman, Syafifa; Ramli, Norazsida; Seman, Mohd Ramli (2017)
Hyperphosphataemia is the key abnormality that sets off a cascade of metabolic events, resulting in bone mineral density of chronic kidney disease (CKD). ESRD patients that undergo PD modalities - Continuous Ambulatory Peritoneal Dialysis (CAPD) uses the peritoneal membrane for solute transfer and ultrafiltration.The differences on the evaluation of peritoneal membrane characteristics can affect the rate of toxin removal – serum phosphorus, from the systems. The purpose of this study was to identify the peritoneal equilibration test (PET) characteristic of CAPD patients, to determine the prevalence of CAPD patients presented with high phosphate level after starting the treatment and to find the significant correlation between the phosphate level and the PET characteristic. The medical records of CAPD patients attending Nephrology Clinic, HTAA from January 2011 and December 2016 were reviewed and recorded. Patients with ESRD who undergo CAPD treatment with age above 18 years old was included. While, non ESRD patients who did not treat using CAPD was excluded. Data were collected successfully from 74 adult CAPD patients with mean age of 51.34 ± 13.75 year old. There were 41 male (55.4%), 33 female (44.6%), 65 Malays (87.8%), 6 Chinese (8.1%) and 3 Indians (4.1%). PET characteristics of CAPD patients showed 11 patients had high characteristic (14.9%), 21 high average (28.4%), 24 low average (32.4%) and 4 low (5.4%). There were 37 CAPD patients (50%) presented with high phosphate level after starting the treatment. Data analysis showed there was a weak, negative correlation between phosphate level and PET characteristics (r = -.232, n = 60, p = 0.070). In conclusion, there was no correlation between phosphate level and PET characteristic. The rate of the toxin removal should not be affected by the differences on peritoneal membrane characteristics.